CLARITY OF REGULATORY OBJECTIVES REGARDING PRESIDENTIAL APPROVAL IN THE FORMATION OF MINISTERIAL / HEAD OF INSTITUTION REGULATIONS - Marianus; Widiarto, Aan Eko; Qurbani, Indah Dwi (The Islamic Education and Multiculturalism Foundation, 2023)
As the holder of power in the administration of government based on the constitution, the president has set a new policy, namely regarding the mechanism for granting presidential approval to draft regulations of ministers or heads of institutions. With the birth of this arrangement, every policy of ministers or heads of institutions with certain criteria must obtain presidential approval before being determined. The mechanism carried out after harmonization has indirectly obscured the stage of forming laws and regulations that are prevalent today. With juridical normative research methods that use statutory, conceptual, and historical approaches, it was found that the arrangement for granting presidential approval actually brought back classic problems. The arrangement is harmonized with other regulations. There is vagueness in sentence formulation, use of words, terms, or phrases, which causes multiple interpretations. The arrangement also comes out of the national policy framework related to simplifying regulations promoted by the president himself. In its formation, there is also the possibility of the influence of bureaucratic political practices or competition among state administrative work units in finding alternative solutions to problems that arise in society.